2019
DOI: 10.15252/embr.201846992
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Experimental Evolution – a proving ground for evolutionary theory and a tool for discovery

Abstract: Microbial experimental evolution uses controlled laboratory populations to study the mechanisms of evolution. The molecular analysis of evolved populations enables empirical tests that can confirm the predictions of evolutionary theory, but can also lead to surprising discoveries. As with other fields in the life sciences, microbial experimental evolution has become a tool, deployed as part of the suite of techniques available to the molecular biologist. Here, I provide a review of the general findings of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 153 publications
(225 reference statements)
0
96
0
Order By: Relevance
“…Experimental evolution is a powerful tool for identification of genetic elements under selection within different environments 4 . Cooper and colleagues recently showed the value of this approach for Streptococcus pneumoniae in mouse models, using a nasopharyngeal colonisation model similar to that described here, but using a 19F pneumococcal strain (BHN97x) 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evolution is a powerful tool for identification of genetic elements under selection within different environments 4 . Cooper and colleagues recently showed the value of this approach for Streptococcus pneumoniae in mouse models, using a nasopharyngeal colonisation model similar to that described here, but using a 19F pneumococcal strain (BHN97x) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between transmission and virulence is well described for a range of pathogens 3 . Experimental evolution approaches 4 have contributed to this understanding, whereby infectious material is passaged from host to host, in an experimental system that promotes gain of infectivity via selection of individuals displaying high levels of in vivo growth. In studies with viral and parasite species, this approach has demonstrated that increased virulence mirrors the increase in transmissibility 5-8 .…”
Section: Introductionmentioning
confidence: 99%
“…Evolution experiments conducted in laboratory environments reproduce key aspects of microbial evolution that are observed in chronic infections and bioreactors (Barrick and Lenski, 2013;Gresham and Dunham, 2014). Certain aspects of genomic and phenotypic evolution in these systems are surprisingly predictable while others are not (Barrick, 2020;Cvijović et al, 2018;Furusawa et al, 2018;McDonald, 2019;Rainey et al, 2017). In theory, profiling many rare mutations in the earliest stages of clonal interference using high-throughput DNA sequencing should allow one to anticipate the future evolution of a population and other populations that evolve in similar environments.…”
Section: Introductionmentioning
confidence: 98%
“…Due to these obstacles, the majority of microbial studies in microfluidic gradients usually do not encompasses cultivations for more than 2 days [ 27,29–32 ] and may not be able to discover adaptations that often manifest themselves only after prolonged cultivation. [ 7,33 ] To overcome these limitations and to enable long‐term ALE experiments with efficient screening under unfavorable high stress conditions, we here describe a novel, robust, and user‐friendly miniaturized ALE chip design that employs adjustable spatial stress profiles and an in‐flow gradient while at the same time enabling efficient on‐chip screening of the complete cell population.…”
Section: Introductionmentioning
confidence: 99%